Communicative Practice of Inheritance of Children outside of Marriage in Mappadaelo Village, Tanasitolo Sub-District according to Islamic Ethics. - Rahmi, Muarifah; Hasan, Hamzah; Talli, Abdul Halim (Jurnal Mercusuar, 2021)
The main objective of this research is to investigate the position, status, and rights of children born out of wedlock based on Islamic law in Mappadaelo village, Tanasitolo district, Wajo regency. The methodological approach used in this research is descriptive qualitative research. The research data is obtained by observing and collecting data from the research field, as well as literature and related documents. The scientific approach used is normative juridical. The findings of this research indicate that children born out of wedlock are not entirely rejected by society. However, acceptance by the local community is conditional on acknowledgment from their biological father to prevent psychological problems. It is also found that, from an Islamic perspective, children born out of wedlock can receive joint inheritance in the form of a gift. The implications of this research are expected to educate the community about the importance of having good behavior and attitudes to reduce cases of free sex and control the presence of children born out of wedlock.